Barriers to Attracting Entrepreneurial Talent: Opportunity for Soft-Landing Programs As a Tool to Stimulate the Entrepreneurial Ecosystem in Peru - Powosino, Ruth (2022)
The start-up industry is proliferating in Latin America, which represents an opportunity to overcome the crisis caused by the COVID-19 pandemic. This research first identifies the  barriers  to  entrepreneurship  in  Peru  by  foreign  female  start-up  founders.  Next,  it  characterizes  the  process  of  start-up  internationalization  and  it  guides  the  design  of  soft-landing  programs  in  Peru.  Finally,  it  discusses  the  opportunity  and  potential  for  attracting   diverse   post-pandemic   COVID-19   entrepreneurial   talent   and   proposes   recommendations for women looking to Peru for internationalization.